Pengukuran Kinerja Keuangan Dengan Rasio Arus Kas Pada Perusahaan Pertambangan yang Terdaftar di BEI - Rachmawati, Yuni; Pamuji, Muhni (Jurusan Akuntansi Politeknik Negeri Padang, 2021)
This research was conducted to determine the financial performance of mining companies listed on the Indonesia Stock Exchange in 2017-2019. Mining companies were selected for research because this industry was not included in the business fields that were reported to support the Indonesian economy in 2019, especially with the outbreak of the Covid-19 pandemic. The high death rate and the rapid spread of this virus have made policies from the government, including limiting activities both domestically and internationally. Even some import-export destination countries have locked down, which of course will affect the productivity and financial performance of the mining industry. From a population of 47 mining companies, only 10 companies met the criteria and were selected as samples. The type of data used is quantitative data. Secondary data sources. Financial performance is measured using a cash flow ratio consisting of 5 liquidity ratios and 2 flexibility ratios. The results showed that based on the cash flow ratio, the majority of mining companies did not have good performance and were still below the standard. Of the eight ratios, only the cash coverage ratio is the most achievable by mining companies. The value of the cash flow ratio of mining companies has decreased during the Covid-19 pandemic.